2001
DOI: 10.1080/13698570120079903
|View full text |Cite
|
Sign up to set email alerts
|

The social construction of risk by community psychiatric nurses and family carers for people with dementia

Abstract: This paper examines the conversational and discursive processes through which situations are constructed as a risk by informal carers and community psychiatric nurses working with people who have dementia. The data were taken from 24 tape recordings of domiciliary meetings between primary informal carers for people with dementia and their community psychiatric nurse (CPN). Data were analysed using techniques developed from conversation analysis and discourse analysis. The analysis identi es four stages associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…Reciprocal (vs non-reciprocal) interaction styles promote patient participation in health counseling sessions, i.e., rigidly following a procedure reduces patients' participation (Poskiparta et al, 2000;Kettunen et al, 2003). With regards to nurse-relative interactions, studies have shown the active role of relatives in risk assessments (Adams, 2001b). Patient relatives are reticent accepting nurses' contributions on non-medical issues (Plumridge et al, 2008).…”
Section: Information Explanation and Advicementioning
confidence: 99%
See 2 more Smart Citations
“…Reciprocal (vs non-reciprocal) interaction styles promote patient participation in health counseling sessions, i.e., rigidly following a procedure reduces patients' participation (Poskiparta et al, 2000;Kettunen et al, 2003). With regards to nurse-relative interactions, studies have shown the active role of relatives in risk assessments (Adams, 2001b). Patient relatives are reticent accepting nurses' contributions on non-medical issues (Plumridge et al, 2008).…”
Section: Information Explanation and Advicementioning
confidence: 99%
“…Horizontal interactional styles between nurses and patients' relatives facilitate the collaborative identification of risk in psychiatric patients (Adams, 2001b), and parents' progressive understanding of their child's diabetes symptoms (Adams, 2001a).…”
Section: Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this approach, the identity of triad members occurs through social practices such as language (Adams, 2000;2001b;Burr, 1996 (Adams, 2000).…”
Section: Trevor Adamsmentioning
confidence: 99%
“…Evidence of this comes from a study of how DCPs organise and manage what they say when they are talking to carers with respect to the construction of identity and risk within dementia care 2001a;2001b).…”
mentioning
confidence: 99%